2018
DOI: 10.3329/bjas.v47i2.40234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apple pomace silage on blood parameters in Suffolk ewe

Abstract: The experiment was carried out to assess the effects of feeding apple pomace silage (APS) on blood parameters in Suffolk ewes. Three ewes were used in 3×3 Latin square design over three periods with three dietary treatments as hay diet, low ethanol APS (L-APS, ethanol 48.7 g kg-1 DM) diet and high ethanol APS (H-APS, ethanol 87.2 g kg-1 DM) diet. Alfalfa hay cube and APS provided half of 110% TDN requirement for APS diets. The area upper or under the curve (AUC) of plasma ethanol was greater (P<0.01) in APS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Both waste apples and by-products provided by the industrialization of this fruit are a potential feed for livestock and contain highly fermentable metabolic substrates (Islam et al, 2018). Apple bagasse is known to be highly acceptable by several livestock species but has a low protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Both waste apples and by-products provided by the industrialization of this fruit are a potential feed for livestock and contain highly fermentable metabolic substrates (Islam et al, 2018). Apple bagasse is known to be highly acceptable by several livestock species but has a low protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, apple pulp is used in the feeding of ruminant animals in the form of fresh, dry and silage (Fontenot et al 1977;Alibes et al 1984;Gasa et al 1992;Kennedy et al 1999;Taasoli and Kafilzadeh, 2008;Ajila et al 2015;Islam et al 2018a). It is very difficult to store the apple pulp due to high moisture content (Alibes et al, 1984;Fang et al 2016;Islam et al 2018b). Therefore, the apple pulp can be preserved by ensiling (McDonald et al, 1991;Fang et al 2016;Islam et al 2018a), since that contains water soluble carbohydrates which is required by lactic acid bacteria to produce lactic acid which is responsible for the decrease in pH of silage (Afzal et al 2015;Skinner et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the apple pulp can be preserved by ensiling (McDonald et al, 1991;Fang et al 2016;Islam et al 2018a), since that contains water soluble carbohydrates which is required by lactic acid bacteria to produce lactic acid which is responsible for the decrease in pH of silage (Afzal et al 2015;Skinner et al 2018). Previous investigations clearly showed that apple pulp silage is an ideal feed for ruminant animals (Rumsey 1978;Pirmohammadi et al 2006;Ajila et al 2015;Islam et al 2018a;Islam et al 2018b;García-Rodríguez et al 2019). Although apple pulp has high energy value, its protein content is low (Gasa et al, 1992;Taasoli and Kafilzadeh, 2008).…”
Section: Introductionmentioning
confidence: 99%